Concentration of Gamma‐Linolenic and Stearidonic Acids as Free Fatty Acids and Ethyl Esters from Viper's Bugloss Seed Oil by Urea Complexation. Issue 10 (14th August 2018) - Rincón‐Cervera, Miguel Ángel; Galleguillos‐Fernández, Raúl; González‐Barriga, Valeria; Valenzuela, Rodrigo; Valenzuela, Alfonso
Abstract : In this work, gamma‐linolenic acid (GLA) and stearidonic acid (SDA) are successfully concentrated as free fatty acids (FFA) and ethyl esters (EE) using the urea complexation method at room temperature and two sources of these fatty acids: commercial Echium plantagineum seed oil as well as extracted oil from this species which is grown in Chile. Concentration factors (% fatty acid in the concentrate/% fatty acid in the original oil) for both fatty acids are found to be between 2.35 and 2.65, although they are more efficiently concentrated as FFA than as EE using both commercial and extracted oils. This is the first work which reports the use of Echium plantagineum seed oil from Chilean origin to produce GLA and SDA concentrates as FFA and EE, with similar results that those obtained with commercial Echium oil. Practical Applications : The interest for GLA and SDA as functional ingredients is increasing in the last few years because of their beneficial effects for human health and their plant origin, as they are mainly provided by seed oils from some Boraginaceae species. In this work, GLA and SDA are selectively concentrated from the rest of fatty acids contained in Echium seed oil by the urea method at room temperature, which is a cheap, safe, and easily scalable process. These concentrates, especially as FFA because of their nutritional characteristics versus EE, may become high added‐value ingredients to be incorporated to functional oils or even substrates for the enzymatic synthesis of structured lipids providing GLA and SDA with a higher bioefficiency than currently available oils. Operational scheme developed in this work which consists of : 1) derivatization of Echium plantagineum oil from two origins (extracted from Chilean seeds and commercial oil) to free fatty acids (FFA) and ethyl esters (EE) and 2) processing of FFA and EE by urea at room temperature to concentrate GLA and SDA. Abstract : Operational scheme developed in this work which consists of : 1) derivatization of Echium plantagineum oil from two origins (extracted from Chilean seeds and commercial oil) to free fatty acids (FFA) and ethyl esters (EE) and 2) processing of FFA and EE by urea at room temperature to concentrate GLA and SDA.